Rab5 and Ndfip1 Are Involved in Pten Ubiquitination and Nuclear Trafficking. (3rd June 2014) - Li, Yijia; Low, Ley‐Hian; Putz, Ulrich; Goh, Choo‐Peng; Tan, Seong‐Seng; Howitt, Jason
<x xml:space="preserve">Abstract</x> The spatial regulation of Pten is critical for its role as a tumour suppressor with both nuclear and cytoplasmic locations being implicated with distinct functions. In the cytoplasm, Pten plays a central role in opposing PI3K/Akt cell signalling, whereas in the nucleus, Pten is important for maintaining genome stability and enhancing the tumour suppressor activity of APC‐CDH1. Despite this diversity in protein function at different subcellular locations, there is limited knowledge on how Pten is able to find different cellular niches. Here, we report that Rab5 GTPase is required for efficient trafficking and ubiquitination of Pten on endosomes inside the cytosol. Using bimolecular fluorescence complementation (BiFC) for imaging protein interactions, we observed that ubiquitinated Pten is localized to peri‐nuclear and nuclear regions of the cell. Nuclear trafficking of Pten required both Rab5 as well as the E3 ligase adaptor protein Ndfip1. Rab5 colocalization with Pten was observed on endosomes and expression of a dominant negative form of Rab5 significantly reduced Pten ubiquitination and nuclear trafficking. Genomic deletion of Ndfip1 abrogated nuclear trafficking of ubiquitinated Pten, even in the presence of Rab5. Our findings show that endosomal trafficking and ubiquitination are important mechanisms for the subcellular distribution of Pten. <inline-graphic xlink:href="ark:/27927/pghmhz08p0" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />